ÂSIM KIRÂATİ'NİN HAFS RİVÂYETİYLE HALEF B. HİŞÂM KIRÂATİ'NİN MUKAYESESİ - KILIÇ, AHMET (Fırat Üniveristesi, 2020)
Hz. Peygamber'in ashabına öğrettiği farklı okuyuşlar kırâat ilminin ortaya çıkmasına kaynak teşkil etmiştir. Her bir sahabî'nin Hz. Peygamber'den Kur'an'ı öğrenip daha sonra farklı bölgelere gidip oralarda başkalarına öğrendiği şekliyle aktarması sonucu her biri doğru ve vahiy ürünü olan kırâat farklılıkları nesilden nesile aktarılmış bize kadar intikal etmiştir. Biz de bu çalışmamızda günümüzde en çok okunan Âsım kırâatinin Hafs rivâyetini ve Halef kırâatini ortaya koymayı ve daha sonra bu iki okuyuş arasındaki usûle ve ferşü'l-hurûf'a dair farklılıkları mukayeseli olarak incelemeyi amaçladık. Çalışmamızın giriş bölümünde kırâat ilmine dair genel bilgilere yer verdik, birinci bölümde Hafs ve Halefin hayatına, ikinci bölümde Hafs ve Halefin usûle dair özelliklerine ve bu usûllerin mukayese edilerek değerlendirilmesine, üçüncü ve son bölümde ise ferşü'l-hurûf'a dair farklılıklara ve bu iki okuyuşu da usûl ve ferş açısından değerlendirmeye yer vererek çalışmamızı sonlandırdık. Okuyuşlar arasındaki bazı farklılıklar Kur'an'ın daha iyi anlaşılmasına katkı sağlayacak ve mana zenginliği oluşacaktır. Ayrıca islamî ilimlerin daha iyi anlaşılmasına öncülük edecektir. Anahtar Kelimeler: Kırâat, Rivâyet, Râvi, Hafs, Halef, Sahîh, Şâz

Introducing accentuation differences by Prophet Muhammad to his companions consituted a source for emerging recitation science. Following learning of Quran by Muhammad and as a result of transfering this instruction by each of companions of Muhammad to particular regions, accentuation differences that of each is accurate and yield of revelation, has been pass down to generations until us. In his study, it is aimed to reveal Hafs narrative of Asım recitation along with Halef recitation and subsequently, differences regarding to observance and particular accentuation between these two recitations will be examined comparatively. In Introduction part of the study, general information related to recitation science was given, first chapter was atrributed to life stories of Hafs and Halef, as second chapter was attributed to specifications of observance and evaluation of these two observances by comparison, in the third and final part of the study was terminated by including differences about particular accentuation an evaluating of these two recitation in the sense of observance and particular accentuation. As a result, some differences in accentuations will contribute to understanding of Quran and create an abundance of denotaion. In addition, it will lead a comprehensive understanding of Islamic sciences. Key Words: Recitation, Narrative, Channel, Hafs, Halef, Authentic Recitation, Exceptional or Irregular Recitation
Comparison of recitation of Halef b. Hişam with hafs narrative of Asım recitation
Keywords: Din